In Vitro Evaluation of Olive Leaf (Olea europaea L.) Extract as a Functional Food Component in Combination with Chemotherapeutics in MCF-7 Breast Cancer Cells - Eda Büker; Fadime Kiran; Seval Taliboglu; Dorina Casoni; Ayşe Ipekel (Pharmaceuticals, 2025)
Background: Since breast cancer is a major cause of mortality, investigation of the synergistic effect of Olea europaea L. leaf extract in combination with some cancer medications is important for obtaining cost-effective and high-achieving treatments for breast cancer. This study aims to investigate the potential effects of Olea europaea L. extract in inhibiting breast cancer cell growth and enhancing the efficacy of chemotherapy agents against breast cancer under in vitro conditions. Methods: We conducted an analysis of some minerals and vitamins of three different viscosities (200 V, 300 V, and 400 V as a natural food product) of Olea europaea L. leaf water-based extract (OWE) derived from a natural cold maceration. We investigated the cytotoxic effects of Olea europaea L. extract with different viscosities (200–400 V) and various chemotherapy agents, either alone or in combination, in estrogen receptor-positive MCF-7 human breast carcinoma cells by MTT assay. Olea europaea L. extract treatment of cells resulted in growth inhibition in a dose- and time-dependent manner. Results: The 400 V OWE showed the highest calcium (301 ± 12 mg/100 g), potassium (1744 ± 33 mg/100 g), and vitamin E (0.36 ± 0.01 mg/100 g) amounts. Based on MTT results, combinations of 400V Olea europaea L. extract, which exhibited the strongest inhibitory effect with an IC50 value of 940 µg/mL, and anticancer drugs were next assessed for their synergistic efficacy towards cell growth inhibition. Conclusions: Combinations of the IC50 value of 400 V OWE with docetaxel, paclitaxel, and trastuzumab (1 µg/mL) treatment showed a strong synergistic effect in the growth inhibition of MCF-7 cells.